The temporal organizing of same-day discharge: A tempography of a Cardiac Day Unit - Vibeke Kristine Scheller (Copenhagen Business School (CBS), 2019)
This dissertation investigates the intersection between time and organizing in a Cardiac Day Unit that introduced same-day discharge schemes for patients with ischemic and arrhythmic heart disease. Same-day discharge has been an influential mega-trend throughout health care sectors in several countries. Introducing same-day discharge schemes comes with the promise of providing both patient-centered care while simultaneously saving expenses for the hospitals and utilizing technological and pharmaceutical innovations. Researchers in various medical fields report that 'quicker is better' for patients, due to the fact that studies show that recovery is faster for patients who were discharged early after surgery. However, the introduction of same-day discharge also introduces organizational challenges, for how is it possible to create a smooth and efficient 'production' line of patients in an uncertain context where changes can happen continuously? What kinds of patient trajectories are produced in the compressed context of same-day discharge? How has an organization such as the Cardiac Day Unit challenged and affected the everyday organizing of patient care by professionals?
hdl:10398/9771
Keywords: 650; Krankenhausmanagement; Krankenhaus; Befragung; Dänemark